Trikotaj matolari naqshlarni shakllantirish va loyihalashda zamonaviy texnika va texnologiyalardan foydalanish (SCIENCE and SOCIETY, 2023)
The article states that scientific and technological development imposes new requirements on the process of creating products and that modern techniques and technologies are used in the formation and design of knitted fabrics. Information is given on the factors taken into account by designers, taking into account the environment, when developing modern new patterned fabrics.